The role of female leadership in the strategic development of family businesses in Kosovo - Turkaj, Fatos; Qosja, Ermira; Shala, Venet (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the role of female leadership in the strategic development of family businesses in Kosovo by analyzing how women in leadership positions influence the shaping and implementation of organizational strategies. Considering the increasing participation of women in entrepreneurship, especially in family businesses, the research seeks to address an important gap in academic literature regarding the transformative capacity of female leadership in contexts influenced by traditional norms and structural gender challenges. Using a quantitative research design, based on data collected from structured questionnaires with women entrepreneurs, this study analyzes the impact of managerial styles, decision-making processes, and strategic approaches on the medium- and long-term performance of family businesses. Inferential statistical analyses, including linear regression and multivariate analysis, were employed to test the relationship between leadership characteristics and strategic development variables such as planning, innovation, digitalization, and access to resources. Preliminary findings suggest that female leadership is characterized by flexibility, inclusion, and a strong orientation toward sustainable and innovative development. The impact of women’s leadership was found to be measurable and positive on the ability of family businesses to adapt long-term strategies in competitive and uncertain environments. This study contributes to advancing academic knowledge on the role of women in the strategic direction of businesses, providing important recommendations for policymakers, support organizations, and entrepreneurs. Furthermore, it highlights the need to reshape societal and institutional narratives that often overlook the value of women’s leadership in economic development.